Coronavirus Disease 2019 (COVID-19) Outbreak Associated With Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) P.1 Lineage in a Long-Term Care Home After Implementation of a Vaccination Program—Ontario, Canada, April–May 2021. (8th July 2021) - Williams, Chantal; Al-Bargash, Dana; Macalintal, Celeste; Stuart, Rebecca; Seth, Anu; Latham, Julienne; Gitterman, Leah; Fedsin, Stephanie; Godoy, Marion; Kozak, Robert; Guthrie, Jennifer L; Wood, Heidi; et al.
Abstract: In a P.1 coronavirus disease 2019 (COVID-19) outbreak in a long-term care home, vaccine effectiveness against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection was 52.5% (95% confidence interval: 26.9%–69.1%) in residents and 66.2% (2.3%–88.3%) in staff. Vaccine effectiveness against severe illness was 78.6% (47.9%–91.2%) in residents. Two of 19 vaccinated resident case patients died. Outbreak management required both vaccination and infection control measures.